2019
DOI: 10.2106/jbjs.18.00509
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Myogenic and Increased Adipogenic Differentiation Capacity of Rotator Cuff Muscle Stem Cells

Abstract: Background: Fat accumulation commonly occurs in chronically torn rotator cuff muscles, and increased fat within the rotator cuff is correlated with poor clinical outcomes. The extent of lipid deposition is particularly pronounced in injured rotator cuff muscles compared with other commonly injured muscles such as the gastrocnemius. Satellite cells, which are a tissue-resident muscle stem-cell population, can differentiate into fat cells. We hypothesized that satellite cells from the rotator cuff have greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, gaining a greater understanding of the nature of how mechanical signals transmitted to tendons result in transcriptional changes would have important implications in the treatment of tendon injuries and diseases. In addition to mechanical signalling events, there are likely to be epigenetic factors that regulate gene expression, as skeletal muscles with different anatomical and functional roles display divergence in their transcriptomes and epigenomes (Terry et al 2018;Gumucio et al 2019;Schubert et al 2019). We found that even though tendons across the body share a common anatomical definition based on their physical location between skeletal muscle and bone, tendon is a surprisingly genetically heterogeneous tissue.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, gaining a greater understanding of the nature of how mechanical signals transmitted to tendons result in transcriptional changes would have important implications in the treatment of tendon injuries and diseases. In addition to mechanical signalling events, there are likely to be epigenetic factors that regulate gene expression, as skeletal muscles with different anatomical and functional roles display divergence in their transcriptomes and epigenomes (Terry et al 2018;Gumucio et al 2019;Schubert et al 2019). We found that even though tendons across the body share a common anatomical definition based on their physical location between skeletal muscle and bone, tendon is a surprisingly genetically heterogeneous tissue.…”
Section: Resultsmentioning
confidence: 84%
“…2019; Schubert et al . 2019). We found that even though tendons across the body share a common anatomical definition based on their physical location between skeletal muscle and bone, tendon is a surprisingly genetically heterogeneous tissue.…”
Section: Resultsmentioning
confidence: 99%
“…There are three types of differentiated adipogenic cells, including white, brown, and beige adipocytes, and the three types are morphologically difficult to recognize; however, a common feature of all adipoblasts is the expression of FABP4 [ 38 , 39 , 40 ]. A study by Schubert et al [ 41 ] on the differentiation capacity of satellite cells from the rotator cuff revealed that all FABP4+ cells were also Pax7-tdTomato+, suggesting that these adipocytes originate from a myogenic progenitor population. Furthermore, in adipogenic media, satellite cells have reduced myogenic differentiation potential, and the expression of the differentiated myocyte marker MRF4 is decreased; accompanied by a significant upregulation of the adipogenesis transcription factor PPAR and FABP4 expression, and increased adipogenic differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…In "The Journal of Bone and Joint Surgery (American volume)", Schubert et al reported that rotator cuff satellite cells are more disinclined to myogenic differentiation, rather prone to adipogenic differentiation compared with that from gastrocnemius muscles (17). By isolation of the specifically labeled satellite cells from rotator cuff muscle and gastrocnemius muscles in tamoxifen-stimulated Pax7 CreERT2 :R26R tdTomato mice, they evaluated the potential of satellite cells to differentiating into myogenic or adipogenic lineage.…”
mentioning
confidence: 99%